Delivering and using 3D models on the web: are we ready? - Roberto Scopigno; Marco Callieri; Matteo Dellepiane; Federico Ponchio; Marco Potenziani (Virtual Archaeology Review)
Digital technologies are now mature for producing high quality digital replicas of Cultural Heritage (CH) assets. The research results produced in the last decade ignited an impressive evolution and consolidation of the technologies for acquiring high-quality digital three-dimensional (3D) models, encompassing both geometry and color. What remains still an open problem is how to deliver those data and related knowledge to our society. The web is nowadays the main channel for the dissemination of knowledge. Emerging commercial solutions for web-publishing of 3D data are consolidating and becoming a de-facto standard for many applications (e-commerce, industrial products, education, etc.). In this framework, CH is a very specific domain, requiring highly flexible solutions. Some recent experiences are presented, aimed at providing a support to the archival of archaeological 3D data, supporting web-based publishing of very high-resolution digitization results and finally enabling the documentation of complex restoration actions. All those examples have been recently implemented on the open-source 3D Heritage Online Presenter (3DHOP) platform, developed at CNR-ISTI.